2018
DOI: 10.1097/md.0000000000013151
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment serum lactate dehydrogenase level in pancreatic cancer patients

Abstract: Background:Several studies were conducted to investigate the prognostic value of pretreatment serum lactate dehydrogenase (LDH) level in pancreatic cancer (PC), but the results were inconsistent. This study aims to comprehensively assess the prognostic value of pretreatment serum LDH level in PC patients by combining the data of the published literatures on this topic.Methods:Embase, PubMed, and Web of Science were completely retrieved until June, 2018. The observational studies focusing on the prognostic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
2
21
1
Order By: Relevance
“…Actually, serum level of LDH signi cantly increases in hypoxic condition, and serves as an indirect marker of tumor hypoxia [25]. For these reasons, the results of our study, consistent with previous reports, also suggested that an elevated serum LDH level might be associated with a poor prognosis [25,28].…”
Section: Discussionsupporting
confidence: 90%
“…Actually, serum level of LDH signi cantly increases in hypoxic condition, and serves as an indirect marker of tumor hypoxia [25]. For these reasons, the results of our study, consistent with previous reports, also suggested that an elevated serum LDH level might be associated with a poor prognosis [25,28].…”
Section: Discussionsupporting
confidence: 90%
“…[ 58 ] Moreover, a recent meta‐analysis has shown a negative correlation between serum LDH levels in pancreatic cancer patients and overall survival, highlighting the prognostic role of this enzyme. [ 59 ] The pleiotropic effects of lactate in the TME are associated with tumor aggressiveness and include fueling tumor cells proliferation, inhibiting antitumor immunity, facilitating invasion, and promoting drug resistance. [ 60 ] In pancreatic cancer, excessive lactate production by hypoxic cancer cells has been shown to support the growth of lactate‐catabolizing normoxic cells and to favor tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…Although there were several meta-analyses to investigate the prognostic values of pretreatment LDH level for cancer patients, [ 45 48 ] only 2 focused on the patients treated with ICIs: one was for non-small-cell lung cancer [ 18 ] and the other was for melanoma. [ 49 ] Also, in the study of Petrelli et al, [ 49 ] the literatures involving all ICIs (including anti-PD-1/PD-L1 monotherapy, anti-CTLA4 monotherapy and combined therapy) were integrated together for meta-analyses.…”
Section: Discussionmentioning
confidence: 99%